Recent Advancement of Transition Metal-mediated Reactions of Diazomethane and (Trimethylsilyl)diazomethane - Muhuri, Sanjukta (Current Organic Chemistry, 2022)
Diazomethane and trimethylsilyl diazomethane are common and versatile reagents in organic synthesis and they are unique as reactants in synthetic methodology. These reagents may be used in esterification, dipolar cycloaddition, epoxidation, aziridination, cyclopropanation, and carbonyl homologation. The lack of practical, scalable methods for the construction of cyclopropanes is a long-standing problem in industrial chemistry and diazomethane/ trimethylsilyl diazomethane has the potential to significantly reduce the cost of bringing new cyclopropane-bearing compounds to market. The transition metal-mediated reactions of diazomethane and trimethylsilyl diazomethane with alkenes, terminal alkynes and carbonyl compounds are being discussed in this article. The mechanism of different coupling, insertion and rearrangement reactions are also explored in this review article. The toxicity and explosive nature of diazomethane/ trimethylsilyl diazomethane are known to all, but concurrently, their efficacy and significant role as the reagents in synthetic transformation can’t be ignored. The untoward properties of diazomethane and trimethylsilyl diazomethane combined with its versatility, make the identification of safe protocols for its use. Considering the importance of these reagents, a concise review is needed. This article will highlight recent metalmediated reactions of diazomethane and trimethylsilyl diazomethane compounds that have been reported from 2000 until 2020.
Keywords: coupling reaction